The emancipatory potential of the Global Studies Programme - Rehbein, Boike (Journal of contemporary African studies, 2023)
Aris Sitas co-founded the Global Studies Programme in 2001 as a cooperation between three world regions (Africa, Asia and Europe) with a focus in the Global South. The programme has become extremely successful and exists up to this day. It was a far-sighted project at the time of its foundation and has enabled hundreds of graduates to engage in a rather special type of intercultural learning.